2014
DOI: 10.1071/bt14081
|View full text |Cite
|
Sign up to set email alerts
|

Plant-level fecundity and andromonoecy in three common (Melaleuca styphelioides, M. thymifolia, M. nodosa) and one rare (M. deanei) Melaleuca (Myrtaceae) species of the Sydney region

Abstract: This paper reports plant-level measures of reproductive performance from large and small field populations of the vulnerable species Melaleuca deanei F.Meull. compared with three common species within the genus: Melaleuca nodosa (Sol. ex Gaertn.) Sm., Melaleuca thymifolia Sm. and Melaleuca styphelioides Sm. Measures reported include average seed numbers per capsule and per plant; average fruit loads per plant; the proportion of buds that become flowers and thence fruits (fruit set); the number of ovules per fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A demographic study confirmed no resource or pollen limitations on fruit set in populations of M. deanei when flowering occurred (Hewitt et al ). However, viable seed loads per unit area were significantly lower in small populations of less than 100 stems (Hewitt et al ), possibly explained by unsuccessful selfing.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…A demographic study confirmed no resource or pollen limitations on fruit set in populations of M. deanei when flowering occurred (Hewitt et al ). However, viable seed loads per unit area were significantly lower in small populations of less than 100 stems (Hewitt et al ), possibly explained by unsuccessful selfing.…”
Section: Resultsmentioning
confidence: 85%
“…When flowering did occur, it was restricted to small numbers of plants per population. Further, significantly lower proportions of plants flower and set fruit within smaller populations, resulting in significantly lower canopy seed loads per square metre in smaller vs. larger populations (Hewitt et al ). While flowering by M. deanei is rare, it is noted to be absent from sites where fire is long absent and most intense across sites in the first two years following fire, or, in those plants heavily pruned under powerline easements or mechanically ‘trittered’ along track edges.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations